GROW: a model for mentorship to advance women's leadership in global health. (22nd April 2018) - Yount, K. M.; Miedema, S.; Krause, K. H.; Clark, C. J.; Chen, J. S.; del Rio, C.
Abstract : In this essay, we discuss the under-representation of women in leadership positions in global health (GH) and the importance of mentorship to advance women's standing in the field. We then describe the mentorship model of GROW, Global Research for Women. We describe the theoretical origins of the model and an adapted theory of change explaining how the GROW model for mentorship advances women's careers in GH. We present testimonials from a range of mentees who participated in a pilot of the GROW model since 2015. These mentees describe the capability-enhancing benefits of their mentorship experience with GROW. Thus, preliminary findings suggest that the GROW mentorship model is a promising strategy to build women's leadership in GH. We discuss supplemental strategies under consideration and next steps to assess the impact of GROW, providing the evidence to inform best practices for curricula elsewhere to build women's leadership in GH.